Through Green’s Three-Dimensional Model: A Newcomer Parent’s Perspectives on Children’s Digital Usage - Liu, Yina; Laidlaw, Linda; Wong, Suzanna (Language and Literacy / Langue et littératie, 2026)
Many Canadian children use digital devices at home. Parents’ perspectives on their children’s digital use influence how those children engage with digital practices and how parents manage them. This article draws on interview data from a larger qualitative study examining first-generation newcomer parents’ perspectives and their children’s digital practices at home in Canada. This paper focuses on the perspectives of a newcomer parent, Diana, regarding her child Jack’s digital practices at home within the Canadian context. Green’s Three-Dimensional Literacy Model is applied to examine how Diana understands and supports Jack’s digital experiences. Diana views Jack’s digital engagement from a holistic perspective, from Green’s operational, cultural, and critical dimensions. Unlike other newcomer parents in my study who primarily emphasized the operational dimension, this paper explores the possible reasons for Diana’s broader view. It also highlights the importance of supporting newcomer parents in developing knowledge about digital literacy and understanding how to help their children become literate in the digital age.